Management of Challenging Esthetic Anterior Cases with Limited Restorative Space: A Clinical Report. Issue 7 (29th January 2018) - Afify, Ahmed; Haney, Stephan
Abstract: With careful restorative planning and surgical placement, dental implants can be used to support and retain a wide range of esthetic prostheses. When implant planning or surgical executions are less than ideal, however, the resulting restorative space can be a significant obstacle to successful treatment. The aim of this article is to describe the use of a customized anterior bar to support a partial overdenture prosthesis for a youthful patient with a high smile line and a limited restorative space of 6 mm. Details of the treatment and an illustration of the customized design are also presented.